The Dynamics of Disparity: A Comprehensive Analysis of the Causes and Consequences of Income and Wealth Inequality and Policy Interventions for Mitigation - Wang, Zhangyifan (Transactions on Economics, Business and Management Research, 2024)
In today’s global economy, economic disparities remain a pressing issue, persisting across different societies. This paper explores the causes, impacts, and potential policy interventions to address income and wealth inequality. The analysis draws on insights from prominent economists such as Darren Acemoglu, James A. Robinson, Joseph E. Stiglitz, Branko Milanovic, Thomas Piketty, and Emanuel Saez. According to the study, globalization, automation, and labor market dynamics are key economic factors driving inequality. In addition, political and social factors, including tax policies, governance models, and access to education and healthcare, significantly impact economic distribution. The consequences of inequality are multifaceted, affecting economic growth, social mobility, social health, and political stability. Furthermore, this paper discusses various policy interventions, such as progressive taxation, improved access to quality education and healthcare, and more robust social safety nets, as potential solutions to mitigate the adverse effects of economic disparities and promote a more equitable distribution of wealth.